"Feasible and effective administration of Bortezomib with Rituximab in children with relapsed/resistant B-cell precursor acute lymphoblastic leukemia (BCP-ALL): A step toward the first line". (3rd October 2019) - Lo Nigro, Luca; Pulvirenti, Giulio; Cannata, Emanuela; Bonaccorso, Paola; Andriano, Nellina; Russo, Giovanna
Abstract: Despite a high cure rate in childhood BCP-ALL, 20% of children still presents with relapse, mostly due to a persistent leukemic clone during the first-line treatment. In this context, obtaining a molecular remission is crucial for reaching a successful allogeneic hematopoietic stem cell transplantation. Bortezomib was effectively administered to children with resistant/relapsed (r/r) BCP-ALL. Moreover, high risk ALL is characterized by the increasing expression of CD20. For the first time we reported two children with r/r BCP-ALL who received a treatment schema including Bortezomib and Rituximab, achieving morphological and molecular remission. Children with high risk features, such as persistent minimal residual disease during induction, will benefit from this combination. Is it time to move toward the first line?